Psychological well-being and body dissatisfaction among Peruvian university students - Duran-Carrillo, Bryan (2024)
Objective. To explore the influence of body dissatisfaction on psychological well-beingamong Peruvian university students. This study followed a quantitative, descriptiveapproach and included a sample of 400 male university students. To measure the variable"body dissatisfaction," the Mental Health Scale (Ryff) was used, comprising 13 items and 4dimensions. Additionally, the Body Shape Questionnaire (BSQ-20) was administered, andstructural modeling analyses were conducted. Results: Psychological well-being showed apositive influence on body dissatisfaction, with B = 0.75. The effect size was considered large,with R² = 0.56. Conclusions: Psychological well-being positively influences body dissatisfactionamong Peruvian university students.